Gene expression of AnnAt1 in different developmental stages of Arabidopsis thaliana exposed to Pb - Phang, Ing Chia; Wan Zakaria, Wan Nor Adibah; Leung, David W. M. (2012)
The toxicity of Pb, its widespread occurrence and persistence highlight the importance of remediation research. Phytoremediation becomes known as a potential remediation tool because it is technically and economically attractive, compared to conventional remediation technologies. However, there is a lack of Pb-related genes. Recently, annexin 1 (AnnAt1) from Arabidopsis thaliana has emerged as a key player in abiotic stresses. Annexins are reported to be related to heat shock proteins, which are the most extensively characterized stress-response genes. A recent study which uses 7-day-old seedlings discovers the participation of AnnAt1 to Pb. Since the expression of AnnAt1 may vary depending on tissue sources, developmental stages, length of exposure, and techniques used, a further experiment was conducted. A real-time PCR study was used to assess the expression of AnnAt1 in different developmental stage of A. thaliana grown in Pb-containing medium.